Muriel Spark, existentialism and the art of death - Craig, Cairns (Edinburgh University Press, 2019)
Proposes that Christian existentialism and, in particular, the work of Søren Kierkegaard, helped shape Spark's religious commitments and her artistic innovations. Because of the prominence, after the Second World War, of the atheistic existentialism of Jean-Paul Sartre, it is often forgotten that existentialism was originally a Christian philosophy, shaped by followers of Kierkegaard such as Karl Jaspers and Gabriel Marcel. The author traces in Spark's writings both the influence of Kierkegaard and of Spark's resistance to Sartre's co-option of existentialism to an atheistic agenda. Kierkegaard's analysis of the nature of the "aesthetic" as a false mode of existence that has to be transcended by the ethical and then by the religious provides a fundamental structure for Spark's satirical analyses of the failings of the modern world